Changing Trends in LIS (Short Communication) - Taneja, S.K. (DESIDOC Journal of Library & Information Technology, 2003)
IT, networking, and the expanding information market-place represent a combination of factors affecting librarians and opinion of administrative decision makers about libraries technological advances affect the fundamental library operations ands can possibly even change the basic social; role of libraries. http://dx.doi.org/10.14429/dbit.17.2.3336